2019
DOI: 10.1103/physrevlett.122.182701
|View full text |Cite|
|
Sign up to set email alerts
|

Measurement of d+Be7 Cross Sections for Big-Bang Nucleosynthesis

Abstract: The cross sections of nuclear reactions between the radioisotope 7 Be and deuterium, a possible mechanism of reducing the production of mass-7 nuclides in Big-Bang nucleosynthesis, were measured at center-of-mass energies between 0.2 MeV and 1.5 MeV. The measured cross sections are dominated by the (d, α) reaction channel, towards which prior experiments were mostly insensitive. A new resonance at 0.36(5) MeV with a strength of ωγ = 1.7(5) keV was observed inside the relevant Gamow window. Calculations of nucl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…Indeed, when switching this reaction on and off in our BBN codes using the FSU rate we obtain a decrease in the final 7 Li/H of 0.7%, in conflict with the 1.4-8.1% decrease reported in Ref. [2]. It is worth noting that the Erratum underestimates the fractional reduction in primordial Li according to its own calculations.…”
contrasting
confidence: 68%
See 2 more Smart Citations
“…Indeed, when switching this reaction on and off in our BBN codes using the FSU rate we obtain a decrease in the final 7 Li/H of 0.7%, in conflict with the 1.4-8.1% decrease reported in Ref. [2]. It is worth noting that the Erratum underestimates the fractional reduction in primordial Li according to its own calculations.…”
contrasting
confidence: 68%
“…These numbers imply an absurdly small uncertainty in the primordial Li abundance prediction when the 7 Be+d rate is neglected. They also imply that by the authors' own calculations the reduction in Li/H for the upper limit of the Rijal et al reaction rate is 9.3%, not the 8.1% given in the Erratum [2].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Their contributions were found to be quite minor [158,159]. An important report from Florida group [160] is that the 7 Be(d,α) reaction might make a remarkable effect on destruction of 7 Be. All other reactions however need to be revisited before making a definite conclusion.…”
Section: Problemsmentioning
confidence: 99%
“…Furthermore, the destructive 7 Be(d, p)2α channel has also been investigated without any significant impact on the lithium problem solution (see Pitrou et al 2018 for details). Most recently, the measurement of Rijal et al (2018) evaluated the impact of a new resonance at ∼360 keV; although it increases the total 7 Be(d, p)2α reaction rate, its contribution is not sufficient for solving the lithium problem. Additional solutions have been proposed, such as the recent study of Hartos et al (2018) to investigate the role of the 11 C levels intervening in the 7 Be(α, γ) 11 C; they concluded that these channels play a minor role in the lithium problem.…”
Section: Introductionmentioning
confidence: 99%